Pengaruh Jenis Stek dan Dosis Pupuk Terhadap Pertumbuhan Tanaman dan Hasil Ubi Jalar (Ipomoea batatas) Aksesi Lasbok - Muhammad Fauzan Farid Al Hamdi (Fakultas Pertanian Universitas Tamansiswa Padang, 2023)
PT Maxindo Karya Anugerah (MAXINDO) is an Indonesia-based snack food manufacturer engaged in tuber-based snacks. One of the types of tubers used is the Lasbok accession sweet potato. The purpose of this study was to determine the best dose of NPK fertilizer and the best cutting source for sweet potato plants, Lasbok accession. The research was conducted in the Katulampa Village, Kec. East Bogor, Bogor City. The experimental design used was a completely randomized block design (split plot) with two factors. The main factor in this study was the dose of NPK fertilizer, while the sub factor in this study was the type of cuttings. Cuttings from tertiary shoots (S3) (89.7 leaves) were significantly higher than cuttings from main shoots (S1) (62.8 leaves) and mid stem (S2) (59.4 leaves) at 45 DAP. S2 has significantly fewer tuber candidates compared to S1 and S3. The tuber weight per plot at the recommended dose (M2) was significantly higher than M0 (control) and M1 (30% below the recommendation) but not significantly different from M3 (30% above the recommendation). The variable number of leaves 45 HST is the variable with the most significant correlation with 5 other variables.